2016
DOI: 10.1002/ece3.2162
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal environment and DNA methylation patterns of estrogen receptor alpha in wild Eastern Bluebird (Sialia sialis) nestlings: a pilot study

Abstract: There is mounting evidence that, across taxa, females breeding in competitive environments tend to allocate more testosterone to their offspring prenatally and these offspring typically have more aggressive and faster‐growing phenotypes. To date, no study has determined the mechanisms mediating this maternal effect's influence on offspring phenotype. However, levels of estrogen receptor alpha (ER α) gene expression are linked to differences in early growth and aggression; thus, maternal hormones may alter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 91 publications
(177 reference statements)
0
31
0
Order By: Relevance
“…Studies in several economically important avian species have shown that maternal exposure to stressors can impact offspring methylation (Liu et al 2018;Zimmer et al 2017), perhaps through the deposition of steroid hormones in the yolk (Ahmed et al 2014;Zimmer et al 2017). These findings are supported by a study on wild Eastern Bluebirds (Sialia sialis), in which yolk testosterone concentration appeared to be positively correlated with density, nestling growth rate and nestling DNA methylation of the diencephalon estrogen receptor alpha promoter (Bentz et al 2016). Since nestling growth rate also increased with percentage DNA methylation (Bentz et al 2016), and avian aggression is typically affected by yolk testosterone level (Eising et al 2006;Muller et al 2009;Partecke and Schwabl 2008;Strasser and Schwabl 2004), it is possible that the females "prepared" their chicks for highdensity conditions (high competition) through testosterone allocation, which instigated changes in DNA methylation.…”
Section: Early Developmental Effectsmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies in several economically important avian species have shown that maternal exposure to stressors can impact offspring methylation (Liu et al 2018;Zimmer et al 2017), perhaps through the deposition of steroid hormones in the yolk (Ahmed et al 2014;Zimmer et al 2017). These findings are supported by a study on wild Eastern Bluebirds (Sialia sialis), in which yolk testosterone concentration appeared to be positively correlated with density, nestling growth rate and nestling DNA methylation of the diencephalon estrogen receptor alpha promoter (Bentz et al 2016). Since nestling growth rate also increased with percentage DNA methylation (Bentz et al 2016), and avian aggression is typically affected by yolk testosterone level (Eising et al 2006;Muller et al 2009;Partecke and Schwabl 2008;Strasser and Schwabl 2004), it is possible that the females "prepared" their chicks for highdensity conditions (high competition) through testosterone allocation, which instigated changes in DNA methylation.…”
Section: Early Developmental Effectsmentioning
confidence: 84%
“…We now know that epigenetic mechanisms contribute to phenotypic variation, and that these mechanisms are often active during development and can be altered in response to different environmental factors (Richards 2006), making them good candidates for the study of the mechanisms behind phenotypic plasticity. These environmental effects include chemicals that are present in the environment, like methyl donors (Weaver 2005), toxic substances (Romano et al 2017;Wallace et al 2018), or external factors such as incubation temperature (Vinoth et al 2018;Yan et al 2015) or maternal effects (Bentz et al 2016). Here, we discuss the role of epigenetic mechanisms in plastic changes within the concept of developmental plasticity, and refer to developmental plasticity as (an) irreversible change(s) in the phenotype resulting from environmentally introduced alterations of development, like early environmental effects (Forsman 2015), parasite load and anthropogenic effects.…”
Section: Environmental Causes Of Variation In Dna Methylationmentioning
confidence: 99%
“…Studies of variation in DNA methylation in free-living vertebrates in an ecological context are lacking (Bentz, Sirman, Wada, Navara, & Hood, 2016;Laine et al, 2016; but see Lea et al, 2016;Liebl, Schrey, Richards, & Martin, 2013;Riyahi, Sanchez-Delgado, Calafell, Monk, & Senar, 2015;Viitaniemi et al, 2019), especially during the critical period of development (but see Rubenstein et al, 2016;Sheldon, Schrey, Ragsdale, & Griffith, 2018). Studies of epigenetics in the wild are essential for understanding the fitness consequences of environmentally induced epigenetic modifications, and they could offer valuable insight into the resilience of populations to environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the range of methylation at CpG1 among individuals was quite narrow (~73-100%), but still significantly correlated to TLR4 expression. Other studies have demonstrated that a similar modest magnitude of difference in DNA methylation can affect gene expression as well as more profound effects on phenotypes (Bentz et al 2016, Rubenstein et al 2016, Verhulst et al 2016, Hu and Barrett 2017. For example, small differences in TLR4 promoter methylation (< 8%) mediated differential resistance to Salmonella enteritidis in domesticated chickens (Gou et al 2012); resistant chickens increased leukocyte TLR4 expression 16 h post-inoculation compared to more modest elevations in susceptible chickens.…”
Section: Sources Of Variation In Tlr4 Expressionmentioning
confidence: 98%